2008
DOI: 10.1038/ejhg.2008.170
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutations to the TSC1 gene cause tuberous sclerosis complex

Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant disorder characterised by the development of hamartomas in a variety of organs and tissues. The disease is caused by mutations in either the TSC1 gene on chromosome 9q34 or the TSC2 gene on chromosome 16p13.3. The TSC1 and TSC2 gene products, TSC1 and TSC2, interact to form a protein complex that inhibits signal transduction to the downstream effectors of the mammalian target of rapamycin (mTOR). Here we investigate the effects of putative TSC1 missense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 29 publications
(27 reference statements)
2
31
1
2
Order By: Relevance
“…The three patients with splice site mutations in the TID without cognitive impairment were noteworthy and future studies should focus on protein studies of splice site mutations to learn more about their effect. The relatively low mean IQ/DQ of the five TSC1 missense mutations conflicts with previous observations of a relatively mild phenotype, 33,37 possibly due to the fact that all of these missense mutations occurred in the N-terminal region, which is essential for TSC1 function. 32,38 Of note is that, excluding splice site mutations, none of the patients with more distal mutations were affected by MR.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The three patients with splice site mutations in the TID without cognitive impairment were noteworthy and future studies should focus on protein studies of splice site mutations to learn more about their effect. The relatively low mean IQ/DQ of the five TSC1 missense mutations conflicts with previous observations of a relatively mild phenotype, 33,37 possibly due to the fact that all of these missense mutations occurred in the N-terminal region, which is essential for TSC1 function. 32,38 Of note is that, excluding splice site mutations, none of the patients with more distal mutations were affected by MR.…”
Section: Discussioncontrasting
confidence: 96%
“…In contrast, missense and other small in-frame mutations may produce an intact, albeit dysfunctional, protein that remains present in the cell with variable remaining function. 32,33 In addition to this 'all-or-nothing' theory, we found that PT mutations occurring in the latter half of TSC2 were associated with significantly higher intellectual outcomes than PT mutations in the first half of the protein, suggesting that mutations in TSC2 which leave the HID intact may result in production of some functional protein. This suggests a third pathophysiological mechanism, applying to distal TSC2 truncating mutations that leave the HID intact and result in appropriate formation of the hamartin-tuberin complex, but perhaps disrupt functions exerted by domains in the distal part of TSC2, such as GAP-expression, transcription and binding of kinases.…”
Section: Discussionmentioning
confidence: 64%
“…In each case, TORC1 activity, as estimated from the ratio of T389 phosphorylated S6K to total S6K, was increased compared to the wild-type control and we classified these variants as pathogenic. Consistent with previous studies [Mozaffari et al, 2009;Nellist et al, 2009], all the variants that were detected at low levels by immunoblotting mapped to the TSC1 N-terminal region (amino acids 50-224) and had a distinct cytoplasmic localization pattern compared to wild-type TSC1, confirming the importance of this region for TSC1 function, localization, and stability [Hoogeveen-Westerveld et al, 2010].…”
Section: Discussionsupporting
confidence: 75%
“…Previously, we used immunoblotting, double-label immunofluorescent microscopy, in-cell Western analysis, and GAP assays to study the effects of 47 TSC2 missense and in-frame insertions/deletions and 26 TSC1 missense and inframe insertions/deletions on TSC1-TSC2 activity [Coevoets et al, 2009;Jansen et al, 2006Jansen et al, , 2008Mozaffari et al, 2009;Nellist et al, 2005Nellist et al, , 2008Nellist et al, , 2009. Pathogenic missense changes in the N-terminal region of TSC1 (amino acids 50-224) reduced TSC1 stability [Mozaffari et al, 2009;Nellist et al, 2009], while pathogenic TSC2 missense changes had distinct effects on the TSC1-TSC2 complex, depending on the region of TSC2 that was affected. Some TSC2 amino acid substitutions prevented TSC1-TSC2 complex formation while others did not affect TSC1-TSC2 binding, but still inactivated the complex .…”
Section: Introductionmentioning
confidence: 99%
“…A reliable functional assay could greatly facilitate the interpretation of variants of uncertain clinical significance. Few TSC1 or TSC2 mutations have been characterized functionally [9][10][11] and it is still impossible to predict phenotypic effects from the location and type of mutation.…”
Section: Introductionmentioning
confidence: 99%